Readiness A Review - Dhingra, Kapil; Yadav, Manjeet (JOURNAL OF INDIAN EDUCATION, 2021)
Readiness is not just a single trait, it encompasses various skills and competencies, presence of which needs to be ensured for appropriate placement of a child. Various educationists have tried to give certain dimensions to this concept. The domains of readiness as identified in various studies conducted in this area are cognitive, social, emotional, motor and language. In addition to these domains, the related factors need to be taken into account while addressing the concept of readiness. Literature review reveals different perspectives and different dimensions in this regard, namely concept of readiness and its domains, factors affecting readiness, class and school readiness, readiness tests and programmeevaluative studies. The present paper reviews the literature on readiness in Indian as well as global context and intends to explain different perspectives in its understanding. Various gaps have been identified in this area, be it the identification and classification of characteristics leading to the accurate, specific and functional definition of the concept of readiness or be it the readiness assessment and programme designing. These gaps need to be addressed in order to cater to the readiness requirements of a child.